The relationship between fuel hedging and operating expenses : Evidence from European and US airline industry - Jaakkola, Eero (My University, 2026)
Aviation industry faces many significant risks; fuel is typically the largest operating cost for airlines. Previous literature presents many valid reasons for airlines to hedge their future fuel needs. Fuel prices are volatile and therefore can cause financial distress to airlines. Fuel hedging is a commonly used risk management tool in the aviation industry. This study examines whether fuel hedging lowers operating expenses. The analysis is based on a panel dataset of 20 airlines in Europe and US and covers the years 2016-2024. The study applies Ordinary Least Squares (OLS) regression models with airline and year fixed effects. Operating costs are measured relative to capacity, and the models control key factors such as fuel prices, load factor, airline size and revenue structure. The results do not provide robust evidence that fuel hedging reduces operating expenses. While some statistically significant relationships appear, they are not consistent across model specifications, and weaken when controlling structural differences, or excluding the COVID period. In addition, hedging shows no significant effect on fuel costs or profitability. In conclusion, findings indicate that fuel hedging acts as a risk management tool to reduce uncertainty of fuel costs.
Keywords: airlines; risk management; operating costs; hedges; aviation; fuels; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance